"Mother" (Mu 母) and the Embodiment of the Dao. Issue 1 (March 2015) - Cook, Constance
Abstract: This article employs newly discovered Warring States texts to reexamine questions regarding the use of the word mother ( mu 母) in the Laozi —did it refer to the feminine role of providing and caring for the descendants of an inherently male cosmic and social order or was it simply a metaphor for an abstract philosophical concept? The author reinforces the latter interpretation suggesting that Mother referred to that existential moment of temporal transition between the cycle of life and death.